ASPECT-BASED SENTIMENT ANALYSIS WITH CATEGORY ENHANCED WORD EMBEDDING AND DEPENDENCY PARSER FOR INDONESIAN REVIEWS - Iswara, Kevin
Determining the right online shop can be done by reading reviews about the shop. Aspect-based sentiment analysis can be used to get public opinions from an online shop by getting conclusions from existing reviews. This final project adapts the research conducted by Wang and Liu (2015) and Cahyadi (2018) in hope to get good results on the aspect-based sentiment analysis on the online shop domain for Indonesian reviews that have been conducted by Fachrina and Widyantoro (2017) and Ilmania , et al (2018).